Alloy melting points data analysis using uncertainty-based sequential probability ratio test. (2nd November 2022) - Aslam, Muhammad
ABSTRACT: The existing sequential probability ratio under classical statistics is applied for testing the null hypothesis when all observations in the data are exact, precise and uncertain. In complex situations, the observations in the data may be imprecise and noted in the intervals. In this case, the existing sequential probability ratio cannot be applied for testing the hypothesis. This paper introduces the sequential probability ratio under neutrosophic statistics to deal with the data having imprecise and uncertain data. The statistic of the proposed test is introduced and applied for testing the hypothesis of alloy melting points data. From the alloy data analysis, simulation study and comparative study, it is concluded that the proposed neutrosophic sequential probability is adequate, informative and suitable to be applied in uncertainty.